A rare case of adult ileo-ileal intussusception secondary to an ileal lipoma - Koay, Kean Leong; Pulandran, Sahilan; Mang Ning, Ong; Juin Yeen, Ooi; Sivananthan, Kinagabran; Thangaratnam, Ramesh R. (International Surgery Journal, 2022)
Intussusception is a common surgical problem among pediatric age group, but the same cannot be said in their adult counterparts. While the disease process is similar in both age groups, the etiopathology and hence the management of this condition differs significantly. In this report, we present a case of an adult female with an ileo-ileal intussusception secondary to a small bowel lipoma, followed by a discussion on the difference of clinical features and management between adults and pediatrics.